Patient exposure levels in radiotherapy CT simulations in Finland. Issue 4 (27th December 2014) - Toroi, P.; Kaijaluoto, S.; Bly, R.
Abstract: Computed tomography (CT)-based simulation is an essential part of the radiotherapy treatment process. Patient exposure levels in CT simulations were collected from 15 CT systems from all 13 Finnish radiation therapy centres. A large standard deviation up to 56 % in dose levels between CT systems was noticed. Average volumetric CT dose indexes (in body phantom) were 24, 18 and 29 mGy for prostate, resection breast and head and neck treatment targets, respectively, and 70 mGy (in head phantom) for whole brain. These average dose indexes were much higher than those in corresponding diagnostic imaging in Finland. Dose levels in simulations with some devices were even over 3-fold higher than the diagnostic reference level for the same area of interest. Moreover, large variations in other exposure parameters, such as pitch and slice thickness, were seen. The results were discussed nationally, and general guidance to optimise dose levels was shared.